A study on the ex-post regulation within the content ecosystem in Korea - Yoon Hyenyoung (International Telecommunications Society (ITS), 2012)
The fixed and mobile contents ecosystem has been recently facing a major change because the importance of contents business is emphasized by the rapid spread of smart media equipments and the accompanying deregulation of related industries leads to more intense competition. With the appearance of gigantic platform operators or network operators, market concentration takes place. Competitions between platform operators and network operators result in unfair trades, which harm both fair competition and user's benefit. Therefore, this paper examines the change of distribution structure within evolved contents ecosystem, understands the causes that harms fair competition, and offers the ex-post regulation policy that will mitigate detected problems. This paper thoroughly analyzes the cases where contents providers experienced unfair trading practices in Korea. However, we propose implications that would establish an effective set of regulations with minimum government control because a unilateral government regulation would harm the development and natural revolution. This research focuses on 1) actual conditions and categories of unfair trade practice in content ecosystem, 2) current polices and the problems of unfair trade practice, and 3) solutions of adopting possible polices that promote fair competition practice in content ecosystem. For this purpose, this study carries out panel studies of related researchers, policy makers, and industry practitioners in Korea.
Keywords: 330